The impact of children's entry to labor market on health expenditures of urban household - Mahdi Shahraki; Simin Ghaderi (Gonabad University of Medical Sciences, 2019)
Child labor is regarded as an ambiguous and controversial challenge encountered in majority of countries across the world. Given the incidence and prevalence of this phenomenon in Iran and the importance of household health expenditures, this study was done to evaluate the impact of children's entry into labor market on household health expenditures. This study was conducted on urban households living in all provinces in Iran in 2016. The sample size was estimated 6517 households. The statistics of these households were extracted from the raw data of income-cost of urban households. The probit and ordered probit econometric models were also used to estimate the coefficients of the model. The results showed that the entry of children into labor markets in both models had a positive impact on household health expenditures. Therefore, making policies for eliminating child labor, compensating the income they got from working, and providing the possibility of further education for these children were of utmost importance. Household income per capita, family size, father's age, and parental education had also a positive and significant effect on household health expenditures. Moreover, parental employment in private sector could increase household health expenditure, but such costs could be decreased if parents were employed in public sector.